Epstein–Barr virus‐induced epigenetic alterations following transient infection. Issue 9 (2nd November 2012) - Queen, Krista J.; Shi, Mingxia; Zhang, Fangfang; Cvek, Urska; Scott, Rona S.
Abstract Epstein–Barr virus (EBV) is a known tumor virus associated with an increasing array of malignancies; however, the association of the virus with certain malignancies is often erratic. To determine EBV's contributions to tumorigenesis in a setting of incomplete association, a transient model of infection was established where a clonal CCL185 carcinoma cell line infected with recombinant EBV was allowed to lose viral genomes by withdrawal of selection pressure. Global gene expression comparing EBV‐negative, transiently infected clones to uninfected controls identified expression changes in more than 1, 000 genes. Among downregulated genes, several genes known to be deoxyribonucleic acid (DNA) methylated in cancer were identified including E‐cadherin and PYCARD. A cadherin switch, increased motility and enhanced cellular invasiveness present in EBV‐positive cells were retained after viral loss, indicating an epigenetic effect. Repression of PYCARD expression was a result of increased promoter CpG methylation, whereas loss of E‐cadherin expression after transient EBV infection did not correlate with increased DNA methylation of the E‐cadherin promoter. Rather, repression of E‐cadherin was consistent with the formation of a repressive chromatin state. Decreased histone 3 or 4 acetylation at the promoter and 5′ end of the E‐cadherin gene was observed in an EBV‐negative, transiently infected clone relative to the uninfected controls. These results suggest that EBV can stably alter gene expression in a heritable fashion in formerly infected cells, whereas its own contribution to the oncogenic process is masked.